The Impact of Epilepsy Education on Knowledge, Self-Management, and Stigma in Individuals With Epilepsy - Kaya, İrem İlgezdi; ÇAVUŞOĞLU, AYSEL; Elmalı, Ayşe Deniz; Bebek, Nerses (Lippincott Williams & Wilkins, 2025)
Background: Epilepsy should be approached in a multidimensional manner, considering its biological, psychological, and social aspects. The aim of this study is to examine the impact of epilepsy education on people with epilepsy regarding knowledge level, self-management, and stigma. METHODS: An online survey, including an epilepsy information form, epilepsy self-management scale, and stigma scale was sent to registered patients in our epilepsy clinic. After the survey, patients were invited to a 1.5-hour epilepsy education program, conducted by 2 instructors on different days, followed by a question-and-answer session. Participants were retested posttraining. RESULTS: Of 265 patients who filled out the pretraining survey, 69 (26%) attended the education program. Those who participated were generally more knowledgeable at the baseline. University graduates and those using the internet as a source of information were more inclined to attend, whereas unmarried individuals attended less. The participant age was 39.1 years (9.2 years), with 61% female, 65% having a university degree, and 61% actively working. Seizure types included focal (45%), generalized (22%), and both (33%), with 70% experiencing less than 1 seizure per month. Posteducation, participants answered more knowledge questions correctly ( P < .001, before: 37.0 [6.0], after: 40.7 [6.1]). Awareness about swimming risks increased in the self-management scale, along with the tendency to carry informative cards, join support groups, and educate relatives. There was no change in the stigma scale. CONCLUSION: Epilepsy education has a positive impact on raising awareness about the disease and promoting self-management in people with epilepsy. The fight against stigma needs to involve broader segments of society.
Keywords: Education Program; Epilepsy; Knowledge; Nursing; Seizure; Self-management; Stigma